E-learning akademicki jako wyzwanie na studiach neofilologicznych - Jedynak, Małgorzata (Neofilolog, 2019)
Internet development enabled e-learning to evolve and assimilate with traditional teaching techniques supporting academic learning. The ad-vantages of e-learning such as its flexibility, reduction of costs, self-paced learning modules or addressing various learning styles are being appreci-ated by more and more universities and colleges. In the theoretical framework the article discusses the basic assumptions of e-learning and organization of distant learning courses. It also presents e-learning from the perspective of English Studies Department students and their needs. Finally, the pilot study is described in which effectiveness of e-learning is examined. Two groups of students were under investigation; one attend-ing regular traditional lectures and the other participating in the e-learning programme. The findings show that e-learning is only slightly more effec-tive than traditional way of teaching. Considering all the limitations of the study, the traditional and innovative ways of teaching deserve to be called equally legitimate.